2021
DOI: 10.1037/lhb0000438
|View full text |Cite
|
Sign up to set email alerts
|

Anchoring effect in legal decision-making: A meta-analysis.

Abstract: Objective: We conducted a meta-analysis to examine whether numeric decision-making in law is susceptible to the effect of (possibly arbitrary) values present in the decision contexts (anchoring effect) and to investigate which factors might moderate this effect. Hypotheses: We predicted that the presence of numeric anchors would bias legal decision-makers' judgment in the direction of the anchor value. We hypothesized that the effect size of anchoring would be moderated by several variables, which we grouped i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 100 publications
3
39
1
Order By: Relevance
“…In particular, numerous studies have investigated the impact of anchoring effects on judicial decisions (see Bystranowski et al, 2021 , for a recent meta-analysis). Judges and jurors are often required to translate qualitative judgments into quantitative decisions ( Hans and Reyna, 2011 ; Rachlinski et al, 2015 ).…”
Section: Justicementioning
confidence: 99%
“…In particular, numerous studies have investigated the impact of anchoring effects on judicial decisions (see Bystranowski et al, 2021 , for a recent meta-analysis). Judges and jurors are often required to translate qualitative judgments into quantitative decisions ( Hans and Reyna, 2011 ; Rachlinski et al, 2015 ).…”
Section: Justicementioning
confidence: 99%
“…For example, Tversky and Kahneman (1974) introduced and empirically tested the anchoring bias (i.e., the tendency to rely too heavily on initial information or salient numbers present in a decision context when making judgments) and the availability bias (i.e., the tendency to overestimate the probability of an event if examples of the event can easily be brought to mind). A recent meta-analysis found evidence of the effect of anchoring bias in legal decision-making, such as decisions made by judges and juries regarding damages awarded in civil cases and the length of prison terms in criminal cases (Bystranowski et al, 2021).…”
Section: What Is Cognitive Bias?mentioning
confidence: 99%
“…For example, the numbers that are presented as anchors are sometimes based on pretests that did not involve anchors (e.g., 15 th and 85 th percentiles; Jacowitz & Kahneman, 1995, p. 1162, they may be based on the true value (e.g., true value ± x or true value × x ±1 ; Röseler, Schütz, Dolling, et al, 2020), or they may have been chosen unsystematically (e.g., two random numbers below and above the true value; Tversky & Kahneman, 1974). However, the choice of anchors has been found to determine effect sizes (e.g., Chapman & Johnson, 1994), and some authors have even suggested that there might be an inverse u-shaped relationship between anchor extremeness and effect sizes, that is, if anchors are too high or too low, their influence might decrease (Bystranowski et al, 2021). Most theories do not yet include paradigm features.…”
Section: Heterogeneity With Uncertain Implicationsmentioning
confidence: 99%
“…Thorsteinson (2011) found nonlinearity, but it was confounded with plausibility. Finally, metaanalyses (Bystranowski et al, 2021;Townson, 2019) have suggested that there may even be an inverted u-shaped relationship.…”
Section: Contradictory Findingsmentioning
confidence: 99%